BIODEGRADASI HERBISIDA 2,4 Dichlorophenoxyaceticacid (2,4- D) OLEH ISOLAT BAKTERI (strain BLM 6-6) DARI TANAH VULKANIK GUNUNG MERAPI, YOGYAKARTA - , SEFTAVI WIDYA SARI, Prof. Dra. Endang S. Soetarto, M.Sc.,Ph.D. ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Chlorinated herbicides especially dichlorophenoxyaceticacid (2,4-D) are one of the synthetic pesticides still being used in Indonesia for agricultural intensification. These herbicides are belonged to the class of organochlorines, recalcitrant and persistent in the soil for about one month.. Only a few types of microbes, especially bacteria were able to degrade the herbicide residues. These studies focused on the biodegradation of dichlorophenoxyaceticacid (2,4-D) herbicides which are most widely applied in the agricultural sector. The purpose of this study was to get the best bacteria able to degradate 2,4-D, to analyze the mechanism of biodegradation of 2,4- D by selected bacterial and to identify these bacteria. These studies used seven types of indigenous soil bacterial isolates (strain BLM 5-3, BLM 6-1, BLM 6-2, BLM 6-3, BLM 6-4, BLM 6-5 and BLM 6-6) from volcanic soil around the slopes of Mount Merapi, Yogyakarta. The first step of the research was to purify all isolates by single cell culture techniques. Their ability to grow in liquid medium containing 2,4-D was determined through the growth experiment. incubated at room temperature for 48 hours. At certain interval of time (1 hour), the isolates growth was measured by spectrophotometry (A600 nm), their activity was determined based on the number of chlorine ions released in the medium using Argentometry method (the titration), isolates that showed the highest activity of chlorine release ion selected and partially identified using standard methods (Bergeyâs Manual of Determinative Bacteria). The results showed that all isolat could grow on liquid medium, but only isolate of BLM 6-6 was able to degrade 2,4-D within seven days and release chlorine ions up to 48 %. The results of the identification of the isolate figured out its characteristic resembled to Pseudomonas sp. the colony was circulair, translucent, baccil, gram negative and able to reduce nitrate.